Impact of Secondary Structure of Toll-Like Receptor 9 Agonists on Interferon Alpha Induction - Yu, Dong (American Society for Microbiology (ASM), 2008)
Oligodeoxynucleotides containing a CpG motif and double- or multistranded structure-forming sequences act as agonists of Toll-like receptor 9 (TLR9) and induce high levels of interferon alpha (IFN-α) in addition to other Th1-type cytokines. In the present study, we evaluated three highly effective IFN-α-inducing agonists of TLR9 to determine the type of duplex structures formed and the agonist's ability to induce immune responses, including IFN-α induction, in human cell-based assays and in vivo in mice and nonhuman primates. Thermal melting studies showed that two of the agonists evaluated had a single melting transition with similar hyperchromicity in both heating and cooling cycles, suggesting the formation of intermolecular duplexes. A third agonist showed a biphasic melting transition in the heating cycle and a monophasic melting transition with lower hyperchromicity during the cooling cycle, suggesting the formation of both intra- and intermolecular duplexes. All three agonists induced the production of Th1-type cytokines and chemokines, including high levels of IFN-α, in human peripheral blood mononuclear cell and plasmacytoid dendritic cell cultures. Subcutaneous administration of the two intermolecular duplex-forming agonists, but not the intramolecular duplex-forming agonist, induced cytokine secretion in mice. In nonhuman primates, the two agonists that formed intermolecular duplexes induced IFN-α and IP-10 secretion. On the contrary, the agonist that formed an intramolecular duplex induced only low levels of cytokines in nonhuman primates, suggesting that this type of structure formation is less immunostimulatory in vivo than the other structure. Taken together, the present results suggest that oligonucleotide-based agonists of TLR9 that form intermolecular duplexes induce potent immune responses in vivo.